Interaction of FUS and HDAC1 Regulates DNA Damage Response and Repair in Neurons - Wang, Wen-Yuan (Nat Neurosci, 2013)
Defects in DNA repair have been extensively linked to neurodegenerative diseases, but the exact mechanisms remain poorly understood. Here, we report that FUS, a RNA/DNA binding protein linked to amyotrophic lateral sclerosis (ALS) and frontotemporal lobar degeneration (FTLD), plays a pivotal role in DNA damage response (DDR). We show that the function of FUS in DDR involves a direct interaction with histone deacetylase 1 (HDAC1), and that the recruitment of FUS to double stranded break (DSB) sites is important for proper DDR signaling. Remarkably, FUS proteins carrying familial ALS (fALS) mutations are defective in DDR and DNA repair, and show a diminished interaction with HDAC1. Moreover, increased DNA damage was also observed in human ALS patients harboring FUS mutations. Our findings suggest that an impaired DDR and DNA repair may contribute to the pathogenesis of neurodegenerative diseases linked to FUS mutations.